Kinetic studies of sodium and metforminium decavanadates decomposition and in vitro cytotoxicity and insulin-like activity - Silva Nolasco, Aniela M. (2020)
The kinetics of the decomposition of 0.5 and 1.0 mM sodium decavanadate (NaDeca) and metforminium decavanadate (MetfDeca) solutions were studied by51V NMR in Dulbecco’s modified Eagle’s medium (DMEM) medium (pH 7.4) at 25◦C. The results showed that decomposition products are orthovanadate [H2VO4]− (V1) and metavanadate species like [H2V2O7]2− (V2), [V4O12]4− (V4) and [V5O15]5− (V5) for both compounds. The calculated half-life times of the decomposition reaction were 9 and 11 h for NaDeca and MetfDeca, respectively, at 1 mM concentration. The hydrolysis products that presented the highest rate constants were V1 and V4 for both compounds. Cytotoxic activity studies using non-tumorigenic HEK293 cell line and human liver cancer HEPG2 cells showed that decavanadates compounds exhibit selectivity action toward HEPG2 cells after 24 h. The effect of vanadium compounds (8–30 µM concentration) on the protein expression of AKT and AMPK were investigated in HEPG2 cell lines, showing that NaDeca and MetfDeca compounds exhibit a dose-dependence increase in phosphorylated AKT. Additionally, NaDeca at 30 µM concentration stimulated the glucose cell uptake moderately (62%) in 3T3-L1 adipocytes. Finally, an insulin release assay in βTC-6 cells (30 µM concentration) showed that sodium orthovanadate (MetV) and MetfDeca enhanced insulin release by 0.7 and 1-fold, respectively.